2020
DOI: 10.5056/jnm19129
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Internal Anal Sphincter Relaxation During High-resolution Anorectal Manometry Is Associated With Peripheral Neuropathy and Higher Charlson Comorbidity Scores in Patients With Defecatory Disorders

Abstract: Background/AimsWe aimed to evaluate associations between comorbidities, peripheral neuropathy, and spontaneous internal anal sphincter relaxation (SAR) in patients with defecatory disorders. MethodsA patient was considered to exhibit SAR during high-resolution anorectal manometry (HR-ARM) when the nadir pressure is < 15 mmHg and the time from onset to relaxation was ≥ 15 seconds in the resting pressure frame. A case-control study was performed using HR-ARM data collected from 880 patients from January 2010 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In our study, TAR patients (median score = 5) had a higher median Charlson comorbidity index score than controls (median score = 4, P = 0.003). 5 Peripheral neuropathy was also significantly more common in TAR patients (39.1%) than in controls (11.6%, P = 0.022). 4 There was a significant difference between the TAR patients (72.7%) and the controls (41.2%) regarding the presence of diseases that potentially cause peripheral neuropathy.…”
Section: To the Editormentioning
confidence: 90%
See 2 more Smart Citations
“…In our study, TAR patients (median score = 5) had a higher median Charlson comorbidity index score than controls (median score = 4, P = 0.003). 5 Peripheral neuropathy was also significantly more common in TAR patients (39.1%) than in controls (11.6%, P = 0.022). 4 There was a significant difference between the TAR patients (72.7%) and the controls (41.2%) regarding the presence of diseases that potentially cause peripheral neuropathy.…”
Section: To the Editormentioning
confidence: 90%
“…In our study, the proportion of constipation among SAR patients was 47.8%. 5 Given that, SAR is unlikely to contribute to FI.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“… 2 Relaxation of the internal anal sphincter (IAS) during anorectal manometry can also occur “spontaneously,” named spontaneous internal anal sphincter relaxation (SAR), when it is not associated with a stimulus. A recent study suggested that such an occurrence of a SAR indicates an “unstable IAS contraction” that “likely plays an important role in the development of fecal incontinence.” 3 Six hundred and one patients with defecation disorders were assessed, only 23 of which exhibited SAR during anorectal manometry. The authors concluded that SAR was associated with neuropathy, 3 but no evidence was presented that there is a causal relationship.…”
Section: To the Editormentioning
confidence: 99%
“…A recent study suggested that such an occurrence of a SAR indicates an “unstable IAS contraction” that “likely plays an important role in the development of fecal incontinence.” 3 Six hundred and one patients with defecation disorders were assessed, only 23 of which exhibited SAR during anorectal manometry. The authors concluded that SAR was associated with neuropathy, 3 but no evidence was presented that there is a causal relationship. The 23 patients were compared with 69 patients without SAR, randomly chosen from the same group.…”
Section: To the Editormentioning
confidence: 99%